The Postmodern Transformation of Language through Social Media, Memes, Emojis, and GIFs: A Study Among Selected North Indian University Students - Reena Nagpal; Ishfaq Ahmad Tramboo; Sinoj Antony (Forum for Linguistic Studies, 2024)
This study explores how digital communication technologies—a consequence of late capitalism—have changed language usage. The study looks at how GIFs, memes, emojis, and social media language have evolved and how postmodern cultural logic is embodied in these forms of communication. Based on Fredric Jameson's theory that postmodernism is the cultural logic of late capitalism, the study highlights the digital forms' inherent fragmentation, intertextuality, and pastiche. It focuses on how language has evolved to reflect postmodern society's hyperreal and dispersed structure by becoming more context-dependent, expressive, and visual. The study employs a mixed-methods approach to examine how social media content is analyzed and to obtain perspectives on various communicative forms from 300 university students in Delhi, Punjab, and Haryana. The findings imply that, in addition to changing language, digital communication technologies have also introduced new forms of expression that combine text, image, and emotion, challenging established linguistic theories. This study advances our knowledge of language in the digital era and has implications for the larger cultural shifts these developments signify.